“Rompe Tabla”: una estrategia para enseñar la tabla periódica de los elementos químicos en grado décimo (2019)
This work focused on a basic but essential theme for the understanding of chemistry, the periodic table. Specifically, it focused on the learning problems on the same in the 10th grade students of the Educational Institution José Acevedo y Gómez, located in the rural area of the municipality of Restrepo, Valle del Cauca. To answer it from a pedagogical approach, the "Break table" strategy was developed, which was based on the pedagogical principles of active learning. The design of the strategy started from a diagnosis that showed the weakness that the students had regarding the knowledge of the periodic table (25.7% correct answers). After the diagnosis, a master class was held to address the issue; After evaluating this process, the strategy "Break table" was applied to guide the same topic "Periodic table of chemical elements". The improvement of the students' performance allowed to demonstrate that the didactic materials, the development of a strategy oriented by the legal requirements, the collaborative work with their respective roles and the motivation of the teacher are fundamental tools for the students to acquire significant learning. The results of the final test (70.3% correct answers) allow to say that the strategy is effective to improve the student’s learning regarding the properties of chemical elements, the way in which the Periodic Table of Chemical Elements is divided, the families of chemists, the concept of ionization energy, the electronic configuration and the period of each element. That is, the active learning manifested in the work with the strategy "Table Break" is a model with which you can work effectively a series of specific knowledge referred to the Periodic Table.